Voltammetric Selectivity in Detection of Ionized Perfluoroalkyl Substances at Micro-Interfaces between Immiscible Electrolyte Solutions - Islam, Gazi Jahirul; Arrigan, Damien (AMER CHEMICAL SOC, 2022)
Widespread contamination by per- and polyfluoroalkyl substances (PFAS) and concern about their health impacts require the availability of rapid sensing approaches. In this research, four PFAS, perfluorooctanoic acid (PFOA), perfluorobutanesulfonic acid (PFBS), perfluorohexanesulfonic acid (PFHxS), and perfluorooctanesulfonic acid (PFOS), were studied at micropipette-based interfaces between two immiscible electrolyte solutions (μITIES) to assess the potentiality for their detection by ion transfer voltammetry. All four PFAS substances were detected by ion transfer voltammetry at the μITIES, with half-wave transfer potentials (E1/2 vs Ag/AgCl) for PFOS, PFHxS, PFBS, and PFOA of 0.34, 0.32, 0.25, and 0.23 V, respectively. The selectivity of the μITIES for detection of PFAS mixtures was investigated. Among the six combinations of the four compounds, most combinations were detectable, except PFOA + PFBS and PFHxS + PFOS, because of unresolved ion transfer voltammograms. These findings provide a basis for the design of new PFAS sensing strategies based on ion transfer voltammetry.